The Role of Compensation Moderates Individual Factors towards Employee Performance at XXX Palembang Company - Eni Cahyani; Avissa Avissa; Efrina Masdaini; Emelda Emelda; Sani Abdullahi Sule (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to determine the effect of work discipline, appreciation, motivation and responsibility on performance. The number of respondents to the research was 66 people, the sampling technique was by applying saturation sampling. The data used is primary data, namely by questionnaire and secondary data. Exogenous variables consist of work discipline, motivation, protection as well as moderating variables while endogenous variables are employee performance. The scale of measurement of indicator variables uses a Likert scale. Data processing is done by calculating using SmartPLS 3.0 software. Data analysis in this study uses the Partial Least Square (PLS) approach. PLS is a structural equation equation model (SEM). Empirical results state that this model is feasible to study, then the results of hypothesis testing reveal that work discipline has a positive effect on performance. Motivation has no effect on performance, it is also revealed that the setting does not moderate work discipline and motivation on performance.